2004
DOI: 10.1074/jbc.m401141200
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and Biochemical Investigations of Kumamolisin-As, a Serine-Carboxyl Peptidase with Collagenase Activity

Abstract: Kumamolisin-As (previously called ScpA) is the first known example of a collagenase from the sedolisin family (MEROPS S53). This enzyme is active at low pH and in elevated temperatures. In this study that used x-ray crystallographic and biochemical methods, we investigated the structural basis of the preference of this enzyme for collagen and the importance of a glutamate residue in the unique catalytic triad (Ser 278 -Glu 78 -Asp 82 ) for enzymatic activity. Crystal structures of the uninhibited enzyme and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 30 publications
4
83
0
Order By: Relevance
“…For instance, it was found that the k cat value for a substrate containing the -ProArg*Gly sequence is ∼65-fold higher than for a substrate containing the -Pro-Gly*Gly sequence and the K M is ∼6.5-fold higher, leading to 10-fold increase of k cat /K M (3). The higher specificity for the substrates with a positively charged residue at P 1 was also confirmed from specificity profile analysis using a peptide library (9). It was suggested in our earlier computational study (16) that the dynamics involving His at P 1 triggered by the bond-breaking and -making events may play an important role in the stabilization of the tetrahedral intermediate and therefore contribute to the relatively high specificity for the substrates with His at P 1 .…”
supporting
confidence: 56%
See 2 more Smart Citations
“…For instance, it was found that the k cat value for a substrate containing the -ProArg*Gly sequence is ∼65-fold higher than for a substrate containing the -Pro-Gly*Gly sequence and the K M is ∼6.5-fold higher, leading to 10-fold increase of k cat /K M (3). The higher specificity for the substrates with a positively charged residue at P 1 was also confirmed from specificity profile analysis using a peptide library (9). It was suggested in our earlier computational study (16) that the dynamics involving His at P 1 triggered by the bond-breaking and -making events may play an important role in the stabilization of the tetrahedral intermediate and therefore contribute to the relatively high specificity for the substrates with His at P 1 .…”
supporting
confidence: 56%
“…The substrate used in the present study, GPH*FF, contains the key residues of the internally quenched fluorogenic (IQF) substrate [NMA-MGPH*FFPK-(DNP)DRDR] used in the earlier experimental study (9,10), although it is considerably smaller. One of the key questions for performing the simulations on kumamolisin-As is how to obtain the coordinates for the substrate (tetrahedral intermediate) in the enzyme complex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism is analogous to the role of, for example, an active site Glu in the first step of the reaction carried out by serine-carboxyl peptidases ( Fig. 8C; Wlodawer et al 2004;Xu et al 2007). Here, the A-1(29OH) to A38(N1) hydrogen bond would be essential to the mechanism; following transfer of the proton from A-1(29OH) to A38(N1) the protonated A38H+ again promotes formation of the active geometry.…”
Section: Discussionmentioning
confidence: 88%
“…In both mechanistic proposals G8, A10, A38, and water 5 stabilize the negative charge accumulated in the transition state. (C) Mechanism proposed for the protein-based serine-carboxyl peptidase kumamolisin-As (Wlodawer et al 2004;Xu et al 2007), analogous to the mechanism in panel B. A glutamate side chain with acidic solution pK a (4.3) acts as both general base and acid by shuttling a proton directly from the serine nucleophile with solution pK a of (z13) to the leaving group during formation of the acylated enzyme.…”
Section: Equilibration and Simulationmentioning
confidence: 99%